Activity of a novel bactericide, zinc thiazole against Xanthomonas oryzae pv. oryzae in Anhui Province of China. (27th October 2014) - Chen, Y.; Yang, X.; Gu, C‐Y.; Zhang, A‐F.; Zhang, Y.; Wang, W‐X.; Gao, T‐C.; Yao, J.; Yuan, S‐K.
Abstract Bacterial leaf blight of rice (BLB), caused by Xanthomonas oryzae pv oryzae, is one of the most serious bacterial diseases in China. Presently, bismerthiazol has been the major bactericide for the control of BLB, however, bismerthiazol‐resistant strains of X. oryzae pv. oryzae have appeared in the field in China. Zinc thiazole is a novel bactericide with strong antibacterial activity against Xanthomonas spp. In this study, sensitivity of 109 X. oryzae pv. oryzae strains to zinc thiazole was determined. The EC50 values for zinc thiazole in inhibiting bacterial growth of the 109 X. oryzae pv. oryzae strains were 0.53–9.62 µg mL−1 with the average EC50 value of 4.82 ± 1.86 µg/ml. The minimum inhibitory concentration (MIC) values of zinc thiazole against the 109 X. oryzae pv. oryzae strains were assessed and the results showed that the MIC values of zinc thiazole for completely inhibiting the growth of these 109 strains ranged from 5.0 to 40.0 µg mL−1. In the evaluation of protective and curative activity test, zinc thiazole exhibited great activity against BLB and provided over 88% control efficacy (at 300 µg mL−1) 1 and 3 days before or after inoculations, which was also higher that that of bismerthiazol in the corresponding treatments. Our field trials showed that zinc thiazole at 375 g.a.i ha−1 provided over 70% control efficacy in 2012 and over 80% control efficacy in 2013 at both sites. Moreover, in all the four field trials, zinc thiazole at 250 g.a.i ha−1 provided higher control efficacy than that of bismerthiazol at 250 g.a.i ha−1. Taken together, zinc thiazole is therefore an alternative tool for the management of BLB.